Simultaneous determination and association between serum levels of irisin and chemerin in PCOS - Hajer Wahbi Abdullateef; Shatha Mohammed Al-khateeb; Esraa Hameed AL-Maini (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the serum levels of irisin, chemerin and insulin in women with polycystic ovary syndrome, and to compare their levels with respect to bodyweight and body mass index. Method: The case-control study was conducted at the Department of Clinical Chemistry, College of Medicine, Mustansiriyah University, Baghdad, Iraq, from December 2020 to February 2022, and comprised healthy controls in group I who were matched for bodyweight and body mass index with polycystic ovary syndrome women in group II. Subjects and cases were inducted using purposive sampling technique Subgroups were also formed on the basis of normal body mass index, and overweight-obese status. Serum irisin, chemerin, insulin and free testosterone levels, anthropometric measurements, lipid profile as well as hormonal and biochemical parameters were noted. Data was analysed using SPSS 25. Result: Of the 88 subjects, 32(36.4%) were in group I with mean age 25.1±4.7 years, and 56(63.6%) in group II with mean age 25.0±6.3 years (p>0.05). Both the groups were divided into two equal subgroups A and B. Group II had significantly higher mean body mass index (p=0.007) and adult body fat (p=0.018). Group II women had significantly high fasting serum insulin levels (p<0.001) and homeostatic model assessment for insulin resistance values (p<0.001). Serum irisin had significant positive correlation with serum chemerin (p=0.014) in group II. Serum free testosterone, irisin and chemerin were significantly higher (p<0.001) in group II compared to group I except for chemerin which showed no significant differences among women with normal body mass index (p=0.071). Conclusion: Serum levels of irisin and chemerin could serve as biomarkers of polycystic ovary syndrome. Key Words: Fibronectins, Insulin, Polycystic Ovary, Overweight, Obesity, Adipose Tissue, Testosterone, Fasting, Lipids.